Factor XIII Deficiency Causing Mutation, Ser295Arg, in Exon 7 of the Factor XIIIA Gene - Anwar, Rashida; Gallivan, Louise; Miloszewski, Krzysztof J. A.; Markham, Alexander F. (Thrombosis and Haemostasis, 2000)
Inherited factor XIII (FXIII) deficiency is an autosomal recessive disorder which results in a serious bleeding diathesis, problems with wound healing and a very high risk of recurrent miscarriage in deficient females. We have analysed the molecular basis of factor XIII deficiency in two patients and their parents, who originate from the North of Pakistan. Four sequence changes were identified: an AGC→AGG (Ser→Arg) FXIII deficiency-causing mutation in codon 295; G→A at position -246 upstream of exon 1; T→C and C→T at positions -23 and -24, respectively, in intron 9. Using molecular modelling we predict that the Ser295Arg mutation would prevent the FXIIIA molecule from folding correctly and thus result in an unstable FXIIIA mutant polypeptide. The sequence changes −246G→A, −23T→C and −24C→T are normal polymorphisms. RT-PCR analysis demonstrates that the intronic sequence changes do not appear to affect the accuracy of FXIIIA RNA processing.
Keywords: Factor XIII; transglutaminase; deficiency; missense mutation